Patient risk factors for conversion during video-assisted thoracic surgery—the Epithor conversion score. (23rd April 2022) - Fourdrain, Alex; Georges, Olivier; Gossot, Dominique; Falcoz, Pierre-Emmanuel; Jougon, Jacques; Baste, Jean-Marc; Marty-Ane, Charles-Henri; Berna, Pascal
Abstract: OBJECTIVES: Intraoperative conversion from video-assisted thoracic surgery (VATS) to thoracotomy may occur during anatomical lung resection. The objectives of the present study were to identify risk factors for intraoperative conversion and to develop a predictive score. METHODS: We performed a multicentre retrospective analysis of French thoracic surgery departments that contributed data on anatomical lung resections to the Epithor database over a 10-year period (from January-2010 to December-2019). Using univariate and multivariate logistic regression analyses, we determined risk factors for intraoperative conversion and elaborated the Epithor conversion score (ECS). The ECS was then validated in a cohort of patients operated on between January- and June-2020. RESULTS: From January-2010 to December-2019, 210, 037 patients had been registered in the Epithor database. Of these, 55, 030 had undergone anatomical lung resection. We excluded patients who had upfront a thoracotomy or robotic-assisted thoracoscopic surgery (n = 40, 293) and those with missing data (6, 794). Hence, 7943 patients with intent-to-treat VATS were assessed: 7100 with a full VATS procedure and 843 patients with intraoperative conversion to thoracotomy (conversion rate: 10.6%). Thirteen potential risk factors were identified among patients' preoperative characteristics and planned surgical procedures and were weighted accordingly to give the ECS. The score showed acceptable discriminatory power (area under the curve: 0.62 in the development cohort and 0.64 in the validation cohort) and good calibration ( P  = 0.23 in the development cohort and 0.30 in the validation cohort). CONCLUSIONS: Thirteen potential preoperative risk factors were identified, enabling us to develop and validate the ECS—an easy-to-use, reproducible tool for estimating the risk of intraoperative conversion during VATS. Abstract : At present, the recommended treatment for early-stage lung cancer is still a combination of anatomical resection (usually lobar) and systematic hilar and mediastinal lymphadenectomy.